THE DEVELOPMENT OF THE FUNCTIONAL MODEL OF THE CONDUCTING ACTIVITIES IN PHARMACIES FOR IMPLEMENTATION OF PHARMACOVIGILANCE - G. Ia. Ibragimova; A. Kh. Gaisarov (Разработка и регистрация лекарственных средств)
In this article the current state of the legal regulations in Russian Federation for pharmacovigilance has been analyzed. The lack of legal regulations of a lot of aspects of holding concrete actions by pharmacists in pharmacies, necessary for further implementation of pharmacovigilance, has been shown. Our functional model of the conducting activities in pharmacies for implementation of pharmacovigilance has been presented. Necessity of presence of the standard operating procedures in pharmacies regulating an order of conducting activities for implementation of pharmacovigilance has been revealed.